Effect of chronic hypoxia on proliferation, apoptosis, and HSP70 expression in mouse bronchiolar epithelial cells - Kim, E. K; Park, J. D; Shim, S. Y; Kim, H. S; Kim, B. I; Choi, J. H; Kim, J. E (Physiological research, 2006)
Heat shock proteins (HSPs) can be induced by various stresses and play an important role in cell cycle progression. HSP70 has been shown to act as an inhibitor of apoptosis. We studied HSP70 expression in bronchial epithelial cells of C57BL/6 mice and homozygous HPS70 knockout mice (hsp70.1–/–) exposed to chronic hypoxic stress. We also investigated changes in cellular proliferation and apoptosis in relation to HSP70. Lungs were removed from mice after a three-week period of exposure to 10 % O2. Immunoblots for HSP70 and immunohistochemical staining for HSP70 and Ki-67 were performed. Apoptosis was assessed using the TUNEL assay. The three-week period of hypoxic stress did not change HSP70 levels in total lung tissue, but a significant reduction in HSP70 expression was observed in bronchiolar epithelial cells. In wild type mice, both HSP70 and Ki-67 expression were significantly reduced in bronchiolar epithelial cells. In homozygous HPS70 knockout mice (hsp70.1–/–), apoptosis of bronchiolar epithelial cells was significantly increased. Our results suggest that HSP70 may exert anti-apoptotic effects in mouse bronchiolar epithelial cells.
Keywords: Animals; proteiny tepelného šoku HSP70; respirační sliznice; apoptóza; proliferace buněk; Cell Hypoxia; Apoptosis; proteiny tepelného šoku HSC70; Epithelial Cells; Immunoblotting; Data Interpretation, Statistical; HSP70 Heat-Shock Proteins; interpretace statistických dat; HSC70 Heat-Shock Proteins; Cell Proliferation; Respiratory Mucosa; imunoblotting; zvířata; Mice, Inbred C57BL; epitelové buňky; hypoxie buňky; myši inbrední C57BL